Heart injury indicators associated with leishmaniosis - Gonçalves da Silva, Eduardo (Pubvet, 2020)
The leishmaniasis is a parasitic zoonosis often fatal caused for the protozoan Leishmania spp., worldwide distributed. The main way of transmission is through the phlebotomine Lutzomyia spp., but there may be other forms of transmission, such as by transfusion blood. The parasite is capable of causing damage to various mammalian organs and, although not common, the disease can cause cardiocirculatory disorders, in which the animal will present common symptoms of heart disease, such as exercise intolerance and dyspnea. Thus, it is important to evaluate the cardiac system in cases of leishmaniasis, through chest radiography, electrocardiogram, cardiac troponin I and CK-MB concentration. So, the goal of this paper is to review the literature according to indicators of cardiac lesions associated with leishmaniasis.
Keywords: Histopathological changes; enzyme concentration; cardiocirculatory disorders; radiographic examination